Consumers' perception of electronic banking service at Hulu Perak / Husni Yakup, Saiful Bahari Ibrahim and Mazlan Ismail - Yakup, Husni; Ibrahim, Saiful Bahari; Ismail, Mazlan (2012)
This paper investigates the factors detennining the Malaysian banking consumers' perception on Electronic Banking (EB) transactions. A research framework was developed to testify the statistical relationships among consumer perceptions on EB transactions. Factor analysis was performed to extract and decide on the number of factors underlying asset of measured variables of interest. This paper also presents the results of research on the consumers' perception of EB facilities among consumers of Maybank Hutu Perak. The research was carried out with the aim of measuring the perception of EB in using the bank facilities provided. With this purpose in mind, a questionnaire was developed and distributed to Maybank's consumers in Hutu Perak area. The data were gathered from the Maybank consumers' data base in Hulu Perak. The data were analyzed using Statistical Package for the Social Sciences (SPSS) and Microsoft Excel were presented using tables and figures. Suggestions on the necessary effort that need to be taken by Maybank Berhad in enhancing the perceptions and overall EB effectiveness are then proposed. It will helps the management of Maybank Berhad that how they can improve the EB services and what are the potential issues or services that should be introduced in society to facilitate the customers in a better way and to compete their rivals in banking industry.